Attitude of medical students towards occupational safety and health : A multi-national study (2015)
Background: Work-related diseases contribute immensely to the global burden of diseases. Better understanding of attitudes of health care workers towards occupational safety and health (OSH) is important for planning.Objective: To assess the attitude of medical students towards OSH around the globe.Methods: A questionnaire assessing the attitude towards OSH was administered to medical and paramedical students of 21 Medical Universities across the globe. In the current study 1895 students, aged 18–36 years, from 17 countries were included. After having performed a principal components analysis, the associations of interest between the identified components and other socio demographic characteristics were assessed by multivariate linear regression.Results: Principal component analysis revealed 3 components. Students from lower and lower-middle-income countries had a more positive attitude towards OSH, but the importance of OSH was still rated higher by students from upper-income countries. Although students from Asian and African continents showed high interest for OSH, European and South-Central American students comparatively rated importance of OSH to be higher. Paramedical students had more positive attitude towards OSH than medical students.Conclusion: The attitude of students from lower-income and lower-middle-income towards importance of OSH is negative. This attitude could be changed by recommending modifications to OSH courses that reflect the importance of OSH. Since paramedical students showed more interest in OSH than medical students, modifications in existing health care system with major role of paramedics in OSH service delivery is recommended. © 2015, Int J Occup Environ Med. All right reserved.